The impact of digital technologies on the information potential of accounting (financial) statements. Part 2: Impact of digital platforms and models on transparency of corporate reporting - M. T. Turmanov; T. M. Rogulenko (Вестник университета)
The relevance of the study is determined by the development of digital technologies in the activities of organizations, which necessitates the use of digital platforms to ensure openness and transparency of company reporting. This article is a continuation of an article published in the journal “Vestnik universiteta” no. 7 of 2022. The article explores the possibilities of increasing the information potential of corporate reporting in the context of objects, processes and commercial relations largescale digitalization. The impact of digital platforms and models on the completeness of the implementation of the principles of transparency in the formation of corporate reporting is determined. The use in the course of the study of general scientific methods of analysis and synthesis, as well as methods of logical comparison, reduction and selection of methodologically important facts of reality, made it possible to conclude that in legal terms, the electronic form of existence of objects, objects, processes is legitimized, and the digital form is a deep care into the virtual world through cryptography, the use of complex systems, encryption code and a limited number of participants. The article critically evaluates the ability of XBRL (eXtensible Business Reporting Language) models to generate transparent reporting. It is assumed that the concept of “digital financial assets” can be formalized as financial instruments with an appropriate interpretation of the results of operations with them in corporate reporting. Unambiguous understanding of new “digital” terms will form a consistent accounting policy of the company and increase, accordingly, the information potential of accounting (financial) statements.